Educational inequalities and regional variation in colorectal cancer survival in Finland - Finke, Isabelle; Seppä, Karri; Malila, Nea; Jansen, Lina; Brenner, Hermann; Pitkäniemi, Janne (Cancer epidemiology, 2021)
Background - Previous studies have reported lower colorectal cancer (CRC) survival in patients with low compared to high educational levels. We investigated the impact of education on CRC survival by using both individual and area-based information on education. - Methods - Patients diagnosed with CRC in Finland in 2007-2016 were followed up for death until the end of 2016. Age-standardized relative survival and relative excess risk of death (RER) were estimated by sex using period approach. RERs were adjusted for age, stage at diagnosis, cancer site, urbanity, hospital district and municipality by using Bayesian piecewise constant excess hazard models. Analyses were conducted including individual (basic, secondary, high) and area-based (quartiles Q1-Q4 based on the proportion of population with basic education) education separately as well as both measures in one model. - Results - We analysed in all 24 462 CRC patients. There was a clear gradient in 5-year relative survival across education groups (men: basic 62 %, secondary 64 %, high 69 %; women: basic 61 %, secondary 67 %, high 71 %). Compared to the basic education group, RER in the high education group was significantly lower. This association was still present after including area-based education in the models (men: RER 0.72, 95 % Confidence interval (CI) 0.64−0.81; women: RER 0.76, 95 % CI 0.59−0.96). Area-based education revealed smaller effect estimates than individual education in CRC survival and no association for men. - Conclusion - Individual education information should be preferred over area-based when survival differences are studied by education. Educational differences in CRC survival are still present in Finland.
Available online 24 November 2020
Gesehen am 09.04.2021